ANALYSIS OF THE NAVAL'S STRATEGIC PLANNING IN FACING MARITIME THREAT TOWARDS INDONESIA AS A WORLD MARITIME AXIS - Trimedianto, Arfin; Ekowati, Masroro Lilik; Umiyati, Sri; Taufik, Wildan; Sulistiyanto, Sulistiyanto (JOURNAL ASRO, 2023)
According to Law Number 29 of 2007, the Provincial Government of the Special Capital Region of Jakarta confirms Jakarta as the State Capital of Indonesia. Based on the SWOT analysis results, researchers found that the relocation of IKN has more strengths and opportunities than weaknesses and threats, so the relocation of IKN is expected to positively impact the Indonesian economy, especially in facing maritime threats. Maritime threats are a global issue that has continued to grow in the last few decades. In the interests of the nation and state, the maritime domain has political, economic, social, and military aspects with very strong weight as tools for developing national interests. The widespread use of the sea in the era of globalization has given rise to various concepts of thought about maritime security. However, from the perspective of a comprehensive approach, maritime security is understood as the combination of preventive and responsive measures to protect the maritime domain against threats and intentional unlawful acts. maritime security challenges and issues include piracy and armed robbery, maritime terrorism, illicit trafficking by sea, small arms and light weapons trafficking, human trafficking, global climate change, and cargo theft. These challenges continue to develop from time to time in various forms. Keywords: Maritime Security, Threats, Prevention Efforts.